Proteomics of human primary osteoarthritic chondrocytes exposed to extremely low-frequency electromagnetic fields (ELF EMFs) and to therapeutic application of musically modulated electromagnetic fields (TAMMEF). (January 2014) - Corallo, Claudio; Battisti, Emilio; Albanese, Antonietta; Vannoni, Daniela; Leoncini, Roberto; Landi, Giacomo; Gagliardi, Assunta; Landi, Claudia; Carta, Serafino; Nuti, Ranuccio; Giordano, Nicola
Abstract Osteoarthritis (OA) is the most frequent joint disease, characterized by degradation of extracellular matrix and alterations in chondrocyte metabolism. Some authors reported that electromagnetic fields (EMFs) can positively interfere with patients affected by OA, even though the nature of the interaction is still debated. Human primary osteoarthritic chondrocytes isolated from the femoral heads of OA-patients undergoing to total hip replacement, were cultured in vitro and exposed 30 min/day for two weeks to extremely-low-frequency electromagnetic field (ELF) with fixed frequency (100 Hz) and to therapeutic application of musically modulated electromagnetic fields (TAMMEF) with variable frequencies, intensities and waveforms. Sham-exposed (S.E.) cells served as control group. Cell viability was measured at days 2, 7 and 14. After two weeks, cell lysates were processed using a proteomic approach. Chondrocyte exposed to ELF and TAMMEF system demonstrated different viability compared to untreated chondrocytes (S.E.). Proteome analysis of 2D-Electrophoresis and protein identification by mass spectrometry showed different expression of proteins derived from nucleus, cytoplasm and organelles. Function analysis of the identified proteins showed changes in related-proteins metabolism (glyceraldeyde-3-phosphate-dehydrogenase), stress response (Mn-superoxide-dismutase, heat-shock proteins), cytoskeletal regulation (actin), proteinase inhibition (cystatin-B) and inflammation regulatory functions (S100-A10, S100-A11) among the experimental groups (ELF, TAMMEF and S.E.). In conclusion, EMFs do not cause damage to chondrocytes, besides stimulate safely OA-chondrocytes and are responsible of different protein expression among the three groups. Furthermore, protein analysis of OA-chondrocytes treated with ELF and the new TAMMEF systems could be useful to clarify the pathogenetic mechanisms of OA by identifying biomarkers of the disease.